Low Carbon Awareness in UTHM Campus - Afandi Fikri, Hilman Hafiz; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2024)
Several ecological issues were brought by Malaysia’s vast expansion, particularly the release of carbon dioxide (Co2). Total carbon emissions from vehicles in year 2023 counted to 291730.650 tones. This proves other causes contribute to carbon emission, such as carbon emission from vehicle smoke, although UTHM uses solar energy as an alternative to reducing carbon. This research explore is based on two objective which are to identify the level of awareness of low carbon practices in UTHM, Parit Raja campus and to recommend the concepts of Low Carbon practices in UTHM, Parit Raja campus. This research focused on the awareness of low carbon in UTHM campus. It also focuses on students and staff, which are 21,158 people, and the sample size is 379 respondents. Quantitative methods were used for data collection by distributing questionnaires to respondents. This study analysed the data using the computer intelligence Statistical Package for Social Science (SSPS) version 26. The data obtained was collected statistically. A descriptive statistical analysis of frequency distribution and mean score is required to determine the level of awareness among students and staff at UTHM campus. The result of the analysis of the level of awareness in environmental aspects is that the highest mean value of 4.06 is in the first place among the other three aspects. The research results for this low carbon practice recommendation show that using Sustainable vehicles has the highest mean value of 4.04 compared to the three low-carbon practices. In conclusion, this research help to increase the awareness to staff and students about low carbon by practicing low carbon practices towards campus sustainability.